Circulating levels of adiponectin and AdipoR expression in peripheral blood mononuclear cells are associated with lower respiratory tract Infection - Qian Wang; Xuemei Wang; Danning Xu; Mengjie Jiang; Yidan Gao; Lijuan Jiang; Meilian Liu; Haoneng Tang; Lingli Tang (Frontiers in Immunology)
ObjectiveThe role of adiponectin (APN) in regulating inflammation is well recognized in metabolic disease, but the dysregulation of APN in lower respiratory tract infection (LRTI) remains controversial. We aimed to measure APN and its signaling receptors, adiponectin receptor (AdipoR), in peripheral blood mononuclear cells (PBMCs) from LRTI patients to explore their potential roles in the LRTI process.MethodsA total of 99 LRTI patients from the Second Xiangya Hospital of Central South University were categorized into acute (n=35) and non-acute (n=64), and non-severe (n=62) and severe (n=37) groups. Serum APN was quantified using ELISA, and mRNA levels of PBMC AdipoRs were determined by RT-qPCR.ResultsBoth levels of APN in circulation and AdipoR1 mRNA were significantly elevated in the LRTI patients (P=2.61E-04; P=2.49E-08), while no statistical difference was observed for AdipoR2. APN levels were increased in the non-acute group compared to the acute group (P=6.06E-04) and AdipoR1 levels were higher in the severe group (P=0.004). Increased APN and AdipoR1 mRNA levels were positively associated with LRTI even after adjustment for sex, age, BMI and blood lipids (OR=1.10; 95% CI 1.04-1.18; P=9.61E-04; OR=2.69; 95% CI 1.29-5.58; P=0.008). Subgroup analyses based on sex, age, and BMI revealed APN elevation in males, ≥65-year-olds, and overweight individuals, with higher AdipoR2 mRNA in females and those under 65; AdipoR1 was uniformly elevated. Additionally, APN was negatively correlated with lymphocyte count in acute and severe subgroup; AdipoR1 was positively correlated with indicators of inflammation in LRTI group.ConclusionOur study highlights that serum APN and AdipoR1 mRNA in PBMCs are associated with LRTI. Circulating APN and PBMC AdipoR1 have different significances in LRTI acute onset and severity.